Approach to Empyema Necessitatis - (:unkn) unknown (SPRINGER, 2011)
Thoracic empyema is a collection of pus in the pleural space. Empyema necessitatis is a rare complication of empyema, characterized by the dissection of pus through the soft tissues of the chest wall and eventually through the skin. We present nine cases of empyema necessitatis, including etiology, duration, and characteristics of clinical history, kind of surgery used, and treatment choices. In a 4-year period nine patients were treated for empyema necessitatis. Six were male and 3 female with an age range of 13-89 years (median = 40 years). Empyema necessitatis was treated with drainage and antibiotherapy or antituberculosis therapy in three patients with the diagnosis of tuberculosis or nonspecific pleuritis. Decortication of the thoracic cavity was used in three patients successfully. Others were treated with open drainage. Final diagnoses were tuberculous empyema in five patients, chronic fibrinous pleuritis in three, and squamous cell carcinoma in one. Except for two patients, one with multisystem failure and one with squamous cell carcinoma, all were discharged with no complications. Surgery plays a critical role in the management of empyema necessitatis in selected patients. Tube drainage, open drainage, and decortication are the choices in variable conditions for obliterating the cavity and regenerating pulmonary function.
Keywords: TUBERCULOSIS